Landscapes of the Islamic World - McPhillips, Stephen.
1 online resource (273 pages)
Keywords: Landscapes of the Islamic World presents new work by twelve authors on the archaeology, history, and ethnography of the Islamic world in the Middle East, the Arabian peninsula, and central Asia. The focus looks beyond the city to engage with the predominantly rural and pastoral character of premodern Islamic society.